Völkisch vs. Catholic Islamophobia in Spain: the Conflict between Racial and Religious Understandings of Muslim Identity - Bravo López, Fernando (Revista de Estudios Internacionales Mediterráneos, 2017)
Abstract This article sets out to demonstrate that considering Islamophobia as a form of racism prevents us from fully grasping the complexity of this phenomenon. The author contends that there are different types of Islamophobia and while some are racist, others are not. To argue this point, he draws on a conflict that was sparked within a Spanish extreme right party revolving around two different conceptions of the human being and society, one rooted in the völkisch tradition and the other in the Catholic tradition. By analyzing the only book the leader of that party wrote, we see how these two conceptions engendered two different types of Islamophobia: one völkisch, the other Catholic. Both share the same vision of Islam as a vital "threat" to the "West", but they differ in their understanding of the foundations of the Muslim and European identities: racist versus religious perspectives. Keywords Islamophobia, racism, Muslims, extreme right, religion Resumen En este artículo se trata de demostrar que considerar que la islamofobia es una forma de racismo impide comprender la complejidad del fenómeno. Se defiende que existen diferentes tipos de islamofobia y que algunos de ellos son racistas, pero que otros no lo son. Para ello, se mostrará que en el seno de un partido español de extrema derecha se produjo un conflicto entre dos concepciones diferentes del ser humano y de la sociedad, una procedente de la tradición völkisch y otra procedente de la tradición católica. Gracias al análisis del único libro que publicó el líder del partido, veremos que de esas dos concepciones se derivaban dos tipos diferentes de islamofobia: una völkisch y otra católica. Ambas compartían una misma visión del islam como una "amenaza" vital para "Occidente", pero diferían en cuanto a cómo entendían los fundamentos de la identidad musulmana y europea: una a partir de presupuestos raciales, la otra a partir de presupuestos religiosos. Palabras clave: islamofobia; racismo; musulmanes; extrema derecha; religión.